Structural dynamics of the N-terminal domain and the Switch loop of Prp8 during spliceosome assembly and activation. Issue 8 (4th April 2018) - Jia, Xu; Sun, Chengfu
Abstract: Precursor message RNA (pre-mRNA) splicing is executed by the spliceosome, a large ribonucleoprotein (RNP) machinery that is comparable to the ribosome. Driven by the rapid progress of cryo-electron microscopy (cryo-EM) technology, high resolution structures of the spliceosome in its different splicing stages have proliferated over the past three years, which has greatly facilitated the mechanistic understanding of pre-mRNA splicing. As the largest and most conserved protein in the spliceosome, Prp8 plays a pivotal role within this protein-directed ribozyme. Structure determination of different spliceosomal complexes has revealed intimate and dynamic interactions between Prp8 and catalytic RNAs as well as with other protein factors during splicing. Here we review the structural dynamics of two elements of Prp8, the N-terminal domain (N-domain) and the Switch loop, and delineate the dynamic organisation and underlying functional significance of these two elements during spliceosome assembly and activation. Further biochemical and structural dissections of idiographic splicing stages are much needed for a complete understanding of the spliceosome and pre-mRNA splicing.